Knowledge, attitude, and practice of working and non-working mothers concerning immunization of underfive children - Muhammad Ali; Ifan Eka Saputra; Adillida Adillida; Sri Sofyani; Iskandar Z Lubis (Paediatrica Indonesiana, 2004)
Objective To compare the knowledge and attitude of working moth-ers (WM) and non-working mothers (NWM) concerning immuniza-tion in children.Methods A cross sectional study was conducted on February, 18-23, 2002 at PT. Olagafood Industri, a noodle manufacture in TanjungMorawa, Medan. Subjects were female workers and non-workingwives of male workers who had under-five-year children. Motherswere interviewed using a questionnaire. Sample size for each groupwas 38. Degree of knowledge, attitude, and practice concerningimmunization were classified into good, insufficient, and bad.Results Mothers’ age, educational level, and children’s age werecomparable between the two groups. Ten WM and 8 NWM hadgood knowledge concerning immunization, which did not differ sig-nificantly (p>0.05). Good attitude toward immunization was foundin 25 WM and 12 NWM; it was a statistically significant difference(p<0.05). The practice of immunization showed similar result asthe attitude. The age of mothers had a significant relationship withthe degree of knowledge and practice, but not with attitude.Conclusion Degree of knowledge about immunization betweenWM and NWM are comparable, but differences exist in their atti-tude and performance